Anticipatory perioperative management for patent ductus arteriosus surgery: Understanding postligation cardiac syndrome. (4th April 2019) - Giesinger, Regan E.; Bischoff, Adrianne R.; McNamara, Patrick J.
Abstract: Ligation of a hemodynamically significant ductus arteriosus results in significant changes in loading conditions which have predictable consequences. Postligation cardiac syndrome, defined as hypotension requiring inotropic support and failure of oxygenation and ventilation, may occur 6‐12 hours following ligation due to left ventricular systolic and diastolic failure, respectively. Afterload is the primary driver of this decompensation. In this review, we describe the pathophysiological changes in loading conditions associated with postligation cardiac syndrome and other contributors to cardiovascular dysfunction following ductal ligation. We present strategies for perioperative optimization and a physiology‐based algorithm for postoperative management guided by targeted neonatal echocardiography. The use of these strategies to reduce the frequency of postligation deterioration may be an avenue to improve outcomes for neonates in this vulnerable patient population.